Proces kontroli w przedsiębiorstwie: Process of control in a company - Kołodziejczyk, Agnieszka (Management and Administration Journal, 2021)
The volatility market and increasing competition make the control more and more important management function. By controlling, a managing staff can notice mistakes and correct actions to achieve the objectives. This article presents the essence of control, characteristic of its types and the analysis of each stages of process control.